Electrochemical analysis of the triarylimidazole-type organic redox catalysts: Chemical stability and homogeneous electron transfer kinetics for the oxidation of 4-methoxybenzyl alcohol. (1st May 2016) - Zhang, Kui-Yong; Lu, Nan-ning; Yoo, Seung Joon; Hu, Li-Ming; Little, R.Daniel; Zeng, Cheng-Chu
Highlights: The current response and reversibility of triarylimidazole-type redox catalysts differs depending upon the nature of the conducting salt and solvent, as well as the concentration of the supporting electrolyte. The best reversibility for the triarylimidazoles could be achieved in 0.05 M LiClO4 /CH3 CN. The electrochemical catalytic efficiency was found to depend upon the peak potential difference between a redox catalyst and the substrate. Abstract: Triarylimidazoles have emerged as novel and useful organic redox catalysts as a result of their straightforward synthesis and tunable oxidation potential. Herein we describe an investigation of the effects of supporting electrolyte and solvent on the chemical reversibility of the triarylimidazole redox couple. Next, the homogeneous electron transfer rate for three triarylimidazole mediators toward the oxidation of 4-methoxybenzyl alcohol was estimated using cyclic voltammetry. The results indicate that the concentration and composition of the conducting salts, especially of the anion, affect the electrochemical performance of the triarylimidazole. Kinetic studies reveal that the smaller the peak potential difference between a mediator and the substrate, the larger the catalytic current and the pseudo first-order homogeneous rate constant.